Wigner function approach to nano device simulation. (15th March 2007) - Kosina, Hans
Coherent transport in mesoscopic devices is well described by the Schrodinger equation supplemented by open boundary conditions. When electronic devices are operated at room temperature, however, a realistic transport model needs to include carrier scattering. In this work, the kinetic equation for the Wigner function is employed as a model for dissipative quantum transport. Carrier scattering is treated in an approximate manner through a Boltzmann collision operator. The development of Monte-Carlo algorithms for this quantum kinetic equation is complicated by the fact that, as opposed to the semi-classical case, the integral kernel is no longer positive. This so-called negative sign problem requires the introduction of new numerical techniques in order to obtain stable Monte-Carlo methods. A particular method for the solution of the stationary Wigner equation is presented. Applications to single barrier and double barrier structures are discussed.